CONCEPTUAL STUDY ON LUTA-VISHA - Angad.Ramesh.Shripat; Shruti.D.Bhokare (International Journal of Applied Ayurved Research, 2017)
Spiders are carnivorous anthropods that coexist with humans. Most of the anthropods transmit communicable diseases. Spiders rarely transmit communicable diseases, but they also play an important role in the ecosystem by consuming other anthropods, such as mosquitoes and flies which transmit diseases. There are more than 30,000 species of spiders and most of them are venomous. Spider bites also called as arachnidism, is an injury resulting by the bite of spider. The epidemiologic analysis of spider bites is confounded by several factors including the extensive differential diagnosis of dermal bite-like lesions, suspected versus definite spider bites and precise identification of spiders by arachnologists. Most of the spider bites are not of importance due to delicate mouthparts and short fangs resulting in lack of substantial envenomation. The differential diagnosis and treatment of spider bite is of vast importance as it includes other anthropod bites, skin infections and exposure to chemical or physical agents. Agada Tantra part of Ayurveda has different approach towards classification of spiders with its clinical features and treatment. In this article an attempt is made to conceptualize spider envenomation according to Ayurveda which will help not only for differential diagnosis of spider bites but also the easy availability of herbal medicine treatment. This article is also helpful in further study to integrate differential diagnosis and treatment approaches of Ayurveda in modern science with the help of phyto-chemical analysis.